Adoption of Umar Bin Abdul Aziz's Principles of Social Justice and Welfare in the Start-up Business Ecosystem - Ardiansyah, Mawar; Hidayati, Tri (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2024)
This article examines the adaptability and application of Umar bin Abdul Aziz's social justice and welfare principles in modern startup business strategies. Umar bin Abdul Aziz is known as one of the fair leaders and focuses on the welfare of society. Through this approach, this article explores how startups can integrate these principles into their business models. This study contributes by providing an ethical framework for startups in Indonesia to not only focus on financial gain but also play an active role in promoting social justice and public welfare. This research is descriptive qualitative research. The sources used are secondary sources. The study uses documentation to find and collect elements or variables related to the study. The analysis method in this study uses descriptive qualitative analysis. The results show that the adoption of the principles of social justice and welfare of Umar bin Abdul Aziz in startup businesses shows that these values are very relevant. Startups can implement a profit-sharing system, establish partnerships with MSMEs, and implement CSR programs to improve community welfare. Financial transparency is also important to prevent corruption, while attention to the welfare of society by offering affordable products can strengthen their contribution to social justice. In this way, business startups gain an ethical framework that not only focuses on financial gain but also plays an active role in the welfare of society, so that public trust in startups can increase.